Proteomic and bioinformatic analysis of membrane proteome in type 2 diabetic mouse liver. Issue 7 (26th February 2013) - Kim, Gun‐Hwa; Park, Edmond Changkyun; Yun, Sung‐Ho; Hong, Yeonhee; Lee, Dong‐Gyu; Shin, Eun‐Young; Jung, Jongsun; Kim, Young Hwan; Lee, Kyung‐Bok; Jang, Ik‐Soon; Lee, Zee‐Won; Chung, Young‐Ho; et al.
Abstract : Type 2 diabetes mellitus (T2DM) is the most prevalent and serious metabolic disease affecting people worldwide. T2DM results from insulin resistance of the liver, muscle, and adipose tissue. In this study, we used proteomic and bioinformatic methodologies to identify novel hepatic membrane proteins that are related to the development of hepatic insulin resistance, steatosis, and T2DM. Using FT‐ICR MS, we identified 95 significantly differentially expressed proteins in the membrane fraction of normal and T2DM db/db mouse liver. These proteins are primarily involved in energy metabolism pathways, molecular transport, and cellular signaling, and many of them have not previously been reported in diabetic studies. Bioinformatic analysis revealed that 16 proteins may be related to the regulation of insulin signaling in the liver. In addition, six proteins are associated with energy stress‐induced, nine proteins with inflammatory stress‐induced, and 14 proteins with endoplasmic reticulum stress‐induced hepatic insulin resistance. Moreover, we identified 19 proteins that may regulate hepatic insulin resistance in a c‐Jun amino‐terminal kinase‐dependent manner. In addition, three proteins, 14–3‐3 protein beta (YWHAB), Slc2a4 (GLUT4), and Dlg4 (PSD‐95), are discovered by comprehensive bioinformatic analysis, which have correlations with several proteins identified by proteomics approach. The newly identified proteins in T2DM should provide additional insight into the development and pathophysiology of hepatic steatosis and insulin resistance, and they may serve as useful diagnostic markers and/or therapeutic targets for these diseases.